Reproduire un cercle et en parler en classe de mathématique : est-ce si simple ? Quelques éléments d’analyse d’une étude didactique comparant trois mises en œuvre d’une même situation - Caroline Bulf; Valentina Celi (Recherches en Éducation)
Interested in the question of the roles of language interactions in the teaching and learning of geometry in primary school, we analyze here the data collected in three different classes where the same problem has been proposed (reproduce a circle). The analyses proposed here reveal potentially differentiating elements in terms of learning coming from a very different implicit knowledge, in the three teachers observed.